Use of supplements by Japanese elite athletes for the Rio de Janeiro 2016 Olympic Games - Yoshino, M.; Inoue, N.; Yoshizaki, T.; Ishibashi, A.; Kondo, E.; Motonaga, K.; Kamihigashi, E.; Kamahara, K.; Kamei, A. (Journal of High Performance Sport, 2020)
Japan Institute of Sports Sciences routinely publishes information about supplements for athletes on its website. This information needs to be regularly updated based on athletes` needs, the International Olympic Committee Consensus Statement, various health hazard reports, and evidence of performance-enhancing effects of supplements used by athletes. We investigated supplement use among 682 Japanese elite athletes who participated in the 2016 Rio de Janeiro Olympic Games. Supplement use was investigated based on a self-reported medical health questionnaire. We observed that 631 (92.5%) athletes used ?1 supplements within the year prior to study enrollment. Amino acids were the most popular supplements consumed by 58.8% of athletes who admitted to supplement use. Recovery from fatigue was the most popular reason cited for supplement use. Among the athletes who used supplements, 57.4% received information regarding supplement use from their coaches, managers, and trainers, and 16.3% received information from healthcare professionals (i.e., physicians, pharmacists, and dietitians). Some athletes were unaware of the types of supplements that they used. A few athletes reported using supplements only because these products were being used by their teammates and admitted that their consumption of supplements was not meant for any particular purpose. This finding indicates that some athletes did not consider the necessity for and effects of supplements before using them. Therefore, athletes should have access to appropriate information regarding supplement use, including the rationale that justifies their consumption, as well as their effectiveness and safety to ensure judicious use of supplements in this population.